Mathematical Applications Of a Rough Topology In Medical Events (COVID19) (Journal of Academic Research, 2021)
This study aims to show that we can use the modern mathematics such as a rough topology to analyze many real life problems. The rough set theory is a good formal tool for processing incomplete information in an information system. The concepts of a rough topology based on the concepts of upper and lower approximations of a given set called universal. Rough set theory use in many areas. Here, we will apply this theory in a new medical event (COVID19). Our work us the rough topology to analyze many real life problems. Our result we try to find the good deciding factor   for the diseases COVID19..